Development and Psychometrics of Instruments to Assess School Personnel’s Bystander Action in Situations of Teen Relationship Abuse and Sexual Assault - Edwards, Katie M. (Journal of interpersonal violence, 2021)
This article describes recently developed instruments that assess school personnel’s bystander barriers and intentions in situations of teen relationship abuse, sexual assault, and sexual harassment, as well as perceptions of school readiness specific to relationship abuse, sexual assault, and sexual harassment prevention and response. Participants were 1,150 high school personnel from 25 schools in New Hampshire, Massachusetts, and Maine. Specific instruments focused on bystander intentions, bystander action, barriers to bystander action, and perceptions of school readiness. Participants were randomly divided into two groups for analysis—the exploratory sample (ES; n = 575) and the confirmatory sample (CS; n = 575). Overall, the measures demonstrated acceptable fit indices. Results suggested that most measures and subscales had adequate reliability, but a few subscales had less than ideal internal consistency, which can likely be attributed to the small number of items. More work is needed, but these measures act as a starting point by which the role of school personnel in prevention initiatives and bystander intervention can be evaluated.